Evaluation of enoxaparin dosing requirements in infants and children - Bauman, Mary E.; Belletrutti, Mark J.; Bajzar, Laszlo; Black, Karina L.; Kuhle, Stefan; Bauman, Michelle L.; Massicotte, M. Patricia (Thrombosis and Haemostasis, 2009)
Increasing the starting dose of enoxaparin results in the early achievement of therapeutic anti-factor Xa levels in children receiving enoxaparin which is critical for effective therapy and the reduction of venipunctures. The aim of this study was: i) to determine the enoxaparin dose required to achieve therapeutic anti-factor Xa levels in infants and children, and ii) to establish whether increasing the starting dose of enoxaparin influenced the time required to reach the therapeutic range and the number of venipunctures required for dose-adjustment, and iii) the radiographic outcome of the thrombosis, where applicable. A retrospective chart review of children who received enoxaparin was carried out at the Stollery Children’s Hospital, Edmonton, Alberta, Canada. Patients treated with standard-dose enoxaparin (1.5 mg/kg for children ≤3 months of age, 1.0 mg/kg for children ≥3 months of age), were compared with children who received a higher initial starting dose of enoxaparin (1.7 mg/kg for children ≥3 months of age, 1.2 mg/kg for children ≥3 months of age). Infants <3 months required an enoxaparin dose of 1.83 mg/kg, and those who received an increased initial enoxaparin dose resulted in faster attainment of therapeutic anti-factor Xa levels requiring significantly fewer venipunctures. Similarly, infants ≥3–12 months, 1–5 years, and 6–18 years, require enoxaparin 1.48 mg/kg, 1.23 mg/kg and 1.13 mg/kg, respectively, in order to achieve a therapeutic anti-factor Xa level. In conclusion, increasing the starting dose of enoxaparin may result in more rapid attainment of therapeutic range with fewer venipunctures, dose adjustments, and without an increase in adverse events.
Keywords: Enoxaparin; children; infants; anti-factor Xa levels; anticoagulation; dosage/adverse effects